The evening light environment in hospitals can be designed to produce less disruptive effects on the circadian system and improve sleep. Issue 3 (21st September 2020) - Vethe, Daniel; Scott, Jan; Engstrøm, Morten; Salvesen, Øyvind; Sand, Trond; Olsen, Alexander; Morken, Gunnar; Heglum, Hanne S; Kjørstad, Kaia; Faaland, Patrick M; Vestergaard, Cecilie L; Langsrud, Knut; et al.
Abstract: Study Objectives: Blue-depleted lighting reduces the disruptive effects of evening artificial light on the circadian system in laboratory experiments, but this has not yet been shown in naturalistic settings. The aim of the current study was to test the effects of residing in an evening blue-depleted light environment on melatonin levels, sleep, neurocognitive arousal, sleepiness, and potential side effects. Methods: The study was undertaken in a new psychiatric hospital unit where dynamic light sources were installed. All light sources in all rooms were blue-depleted in one half of the unit between 06:30 pm and 07:00 am (melanopic lux range: 7–21, melanopic equivalent daylight illuminance [M-EDI] range: 6–19, photopic lux range: 55–124), whereas the other had standard lighting (melanopic lux range: 30–70, M-EDI range: 27–63, photopic lux range: 64–136), but was otherwise identical. A total of 12 healthy adults resided for 5 days in each light environment (LE) in a randomized cross-over trial. Results: Melatonin levels were less suppressed in the blue-depleted LE (15%) compared with the normal LE (45%; p = 0.011). Dim light melatonin onset was phase-advanced more (1:20 h) after residing in the blue-depleted LE than after the normal LE (0:46 h; p = 0.008). Total sleep time was 8.1 min longer ( p = 0.032), rapid eye movement sleep 13.9 min longer ( p < 0.001), and neurocognitive arousal was lower ( p = 0.042) in the blue-depleted LE. There were no significant differences in subjective sleepiness ( p = 0.16) or side effects ( p = 0.09). Conclusions: It is possible to create an evening LE that has an impact on the circadian system and sleep without serious side effects. This demonstrates the feasibility and potential benefits of designing buildings or hospital units according to chronobiological principles and provide a basis for studies in both nonclinical and clinical populations.